2021
DOI: 10.1002/bit.27954
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of self‐standing and vascular supportive multimaterial hydrogel structures for organ engineering

Abstract: Three dimensional printable formulation of self‐standing and vascular‐supportive structures using multi‐materials suitable for organ engineering is of great importance and highly challengeable, but, it could advance the 3D printing scenario from printable shape to functional unit of human body. In this study, the authors report a 3D printable formulation of such self‐standing and vascular‐supportive structures using an in‐house formulated multi‐material combination of albumen/alginate/gelatin‐based hydrogel. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…The mechanical properties of the scaffolds were measured by using a WDW‐1 material testing machine (Songdun Machine Equipment Co., Ltd, Shanghai, China) according to previous protocol. [ 50 ] To capture the stress‐strain curves, the crosslinked 3D grid scaffolds (15 × 15 × 5 mm 3 ) were placed between two compression plates, a constant compression speed of 0.2 mm min −1 was applied until the scaffolds were broken. Then the compression modulus was obtained from the slope of the linear region of the stress‐strain curves, and the ultimate strength and failure strain were measured from the data of the broken state.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical properties of the scaffolds were measured by using a WDW‐1 material testing machine (Songdun Machine Equipment Co., Ltd, Shanghai, China) according to previous protocol. [ 50 ] To capture the stress‐strain curves, the crosslinked 3D grid scaffolds (15 × 15 × 5 mm 3 ) were placed between two compression plates, a constant compression speed of 0.2 mm min −1 was applied until the scaffolds were broken. Then the compression modulus was obtained from the slope of the linear region of the stress‐strain curves, and the ultimate strength and failure strain were measured from the data of the broken state.…”
Section: Methodsmentioning
confidence: 99%
“…These structural limitations may be circumvented by printing the ink into a support matrix, which is often also a self-healing hydrogel or a suspension bath. ,, The printing nozzle is dragged through the support matrix which temporarily fluidizes followed by rapid self-healing to confine and support the printed structure. Using this freeform 3D printing, also termed as freeform reversible embedding or fluid bath-assisted 3D printing, complex branched structures can be printed at full structural freedom beyond the technological limitations of traditional layer-by-layer deposition. ,, This highly attractive feature is exploited in particular to print vascularized structures that facilitate nutrient and waste transport as shown in Figure C, which has been a notorious bottleneck for the design of tissue constructs. , Furthermore, more liquid low-viscosity inks that are not stable during extrusion 3D printing can be employed in freeform 3D printing due to the structural support of the matrix, thereby increasing the palette of potential ink formulations. , The printed ink can be cured followed by removal of the support matrix (support bath-enabled 3D printing). Alternatively, the support matrix may be cured (embedded 3D printing) and the printed ink may be removed (sacrificial ink) or left in place (functional ink) .…”
Section: Self-healing Injectable Hydrogels For 3d (Bio)printingmentioning
confidence: 99%
“…119 Nevertheless, significant progress has already been made in this area recently. 60,61,[122][123][124] Lee et al demonstrated, as a proof of concept, the application of a human recombinant elastic bio-ink with which they could bioprint a vascularized cardiac construct that displayed the endothelium barrier function. 125 Therefore, constructing complex hierarchical vascularized networks in bioprinted tissue construct and establishing a connection with the host by surgical anastomosis or other technical solutions are issues that need to be addressed urgently.…”
Section: Clinical Translation Of Bioprinted Productsmentioning
confidence: 99%